P189 Antiphospholipid antibodies and vascular renal lesions as prognostic factors in lupus nephritis. (23rd March 2020) - Paglionico, Annamaria; Varriano, Valentina; Petricca, Luca; Marioa, Clara Di; Gigante, Maria Rita; Tanti, Giacomo; Tolusso, Barbara; Ferraccioli, Gianfranco; Gremese, Elisa
Abstract : Purpose: To determine the role of antiphospholipid antibodies (aPL) and vascular renal lesions on renal prognosis, in terms of time to achieve remission, number of renal flares and development of chronic renal damage in patients with lupus nephritis (LN). Methods: 91 consecutive LN patients have been evaluated and the follow-up data have been collected at the baseline and at 6, 12, 24 months and at the last follow-up visit. Histopathological data of 41 patients were evaluated according to the 2016 revision of ISN/RPS classification. Results: Among the 91 LN patients, 31(34.1%) were aPL positive (aPL+), 10(32.2%) of them were affected by Antiphospholipid Antibodies Syndrome (APS), 53.3% showed a single aPL positivity, 23.1% double aPL positivity and 15.4% triple aPL positivity. At the last follow up visit a significant higher number of aPL+ patients showed a persistent complement consumption than aPL negative (aPL-) patients (p=0.001). We observed that aPL- patients showed a remission achievement time slightly earlier than aPL+ patients (13.6±1.0 months vs 16.5±1.5 months; log-rank test: p=0.06, Breslow test: p=0.08) and as expected, patients with a persistent complement consumption achieve remission later (18.2 ±1.5 months vs 13.0±1 months; log-rank test: p=0.002, Breslow test: p=0.003). Furthermore at the last follow up, a significant higher percentage of aPL+ patients developed persistent proteinuria (p=0.02) and chronic renal failure (p=0.04). Considering histolopathologic features we didn't observe significant differences between aPL+ and aPL- patients but we found two typical vascular lesions (mesangiolysis and vascular thrombi) only in aPL+ patients. Conclusion: Apl positivity is a predictor of worse renal outcome but in our cohort we didn't find an association between aPL positivity and vascular renal lesions at renal biopsy. The worse renal outcome and the late time to achieve remission in aPL+ group can be related to a cumulative vascular damage over time.